Analisis Kinerja Keuangan Terhadap Harga Saham pada Industri Loga yang Terdaftar Di BEI - Sauqi, Muhammad Irfan; Wahyuningtyas, Endah Tri; Agustina, Heni (EQUITY, 2019)
The purpose of this study is to determine the financial effect proxy through Current  ratio, Debt Equity Ratio, Return On Asset, Return On Equity, Return On Investment and Net Profit Margin Against Stock Price of the Company and the like mentioned in Indonesia Stock Exchange. The sample used in the study amounted to 16 companies from a total of 18 companies, for the techniques used in the study using multiple regression analysis. The test results show the variable Current Ratio, Debt Equity Ratio, Return On Asset, Return On Equity, Return On Investment and Net Profit Margin simultaneously affect the stock price of metal companies and the like listed on the Indonesia Stock Exchange, with the results obtained F- count as 5,948 with  significant 0.000 < 0.05. Which means the relationship between the independent variables Current Ratio, Debt Equity Ratio, Return On Asset, Return On Equity, Return On Investment and Net Profit Margin together have a close relationship to stock prices.